2023
DOI: 10.1002/ejhf.3077
|View full text |Cite
|
Sign up to set email alerts
|

Impact of vasodilators on diuretic response in patients with congestive heart failure: A mechanistic trial of cimlanod (BMS‐986231)

Pierpaolo Pellicori,
John G.F. Cleland,
Maria Borentain
et al.

Abstract: AimTo investigate the effects of Cimlanod, a nitroxyl donor with vasodilator properties, on water and salt excretion after an administration of an intravenos bolus of furosemide.Methods and resultsIn this randomized, double‐blind, mechanistic, crossover trial, 21 patients with left ventricular ejection fraction <45%, increased plasma concentrations of N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) and receiving loop diuretics were given, on separate study days, either an 8 h intravenous (IV) infusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…The STAND-UP AHF trial 12 demonstrated that cimlanod was well tolerated, provided expected vasodilatory and decongestive effects, but those benefits did not persist beyond 48-h duration of treatment, while the StandUP Imaging trial 13 showed improvements in left ventricular end-systolic dimensions and stroke volume indices comparable to nitroglycerin, without additional inotropic or lusitropic effects, in a small cohort of chronic HF patients. The most recent cimlanod study published by Pellicori et al 14 in this issue of the Journal is timely, building upon the STAND-UP programme and offers both the mechanistic insights into the limitations of vasodilator therapy in acutely decompensated HF and an explanation of the potential lack of benefit noted in clinical trials as well as previous observations of deleterious effects on renal function. 14 This elegant study evaluated the more mechanistic effects of cimlanod on both the arterial and venous vasculature, renal function, and diuresis.…”
mentioning
confidence: 97%
See 4 more Smart Citations
“…The STAND-UP AHF trial 12 demonstrated that cimlanod was well tolerated, provided expected vasodilatory and decongestive effects, but those benefits did not persist beyond 48-h duration of treatment, while the StandUP Imaging trial 13 showed improvements in left ventricular end-systolic dimensions and stroke volume indices comparable to nitroglycerin, without additional inotropic or lusitropic effects, in a small cohort of chronic HF patients. The most recent cimlanod study published by Pellicori et al 14 in this issue of the Journal is timely, building upon the STAND-UP programme and offers both the mechanistic insights into the limitations of vasodilator therapy in acutely decompensated HF and an explanation of the potential lack of benefit noted in clinical trials as well as previous observations of deleterious effects on renal function. 14 This elegant study evaluated the more mechanistic effects of cimlanod on both the arterial and venous vasculature, renal function, and diuresis.…”
mentioning
confidence: 97%
“…The most recent cimlanod study published by Pellicori et al 14 in this issue of the Journal is timely, building upon the STAND-UP programme and offers both the mechanistic insights into the limitations of vasodilator therapy in acutely decompensated HF and an explanation of the potential lack of benefit noted in clinical trials as well as previous observations of deleterious effects on renal function. 14 This elegant study evaluated the more mechanistic effects of cimlanod on both the arterial and venous vasculature, renal function, and diuresis. 14 Patients with left ventricular systolic dysfunction (left ventricular ejection fraction <40%) were administered intravenous furosemide after an infusion of the study drug or placebo.…”
mentioning
confidence: 97%
See 3 more Smart Citations